The Relationship Between Onychomycosis infections and Diabetes: Risks and Management: Review: Hubungan Antara Infeksi Onikomikosis dan Diabetes: Risiko dan Manajemen: Ulasan - Wali, Nahrawaan M. (Indonesian Journal on Health Science and Medicine, 2025)
Diabetes mellitus is a very frequent chronic condition globally, presenting a substantial health issue due to its severe effects on several body processes and its correlation with different consequences. Among these problems, onychomycosis, or fungal nail infections, is a prevalent yet sometimes disregarded illness that can substantially impact patients' quality of life and general health. Onychomycosis is a fungal infection that affects the nail structure, resulting in discoloration, thickness, and occasionally total loss of the nail. The likelihood of getting onychomycosis is significantly increased in diabetic individuals due to weakened immune response, poor circulation, and consistently high blood glucose levels, which provide an optimal environment for fungal proliferation. This review seeks to examine the complex link between diabetes mellitus and onychomycosis, emphasizing the underlying processes, risk factors, and clinical consequences of this interaction. Moreover, it underscores the significance of prompt identification and efficient therapy options to alleviate the effects of this illness and enhance patient outcomes. Highlights: Diabetics risk infection — 3× higher onychomycosis, ulcers, amputations risk. PAS stain best — 92% sensitivity, superior to culture and KOH. Combo therapy works — Oral terbinafine + topical boosts cure rates. Keywords: Onychomycosis, Diabetes, Antifungal Treatment, Diagnosis, Complications